2001
DOI: 10.1046/j.1468-8123.2001.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of a karst aquifer by hydrothermal fluids: evidence from stable isotopic compositions of cave mineralization

Abstract: Mineral deposits in the Cupp‐Coutunn/Promeszutochnaya cave system (Turkmenia, central Asia) record a phase of hydrothermal activity within a pre‐existing karstic groundwater conduit system. Hydrothermal fluids entered the caves through fault zones and deposited sulphate, sulphide and carbonate minerals under phreatic conditions. Locally, intense alteration of limestone wall rocks also occurred at this stage. Elsewhere in the region, similar faults contain economic quantities of galena and elemental sulphur min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 56 publications
4
18
0
1
Order By: Relevance
“…The purpose of this paper is to demonstrate that stable isotope data are a valuable geochemical tool to identify and quantify palaeowater-rock interactions in low-temperature hydrothermal karst systems (e.g. Bakalowicz et al 1987;Bottrell et al 2001;Plan et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this paper is to demonstrate that stable isotope data are a valuable geochemical tool to identify and quantify palaeowater-rock interactions in low-temperature hydrothermal karst systems (e.g. Bakalowicz et al 1987;Bottrell et al 2001;Plan et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It could also be modified in response to water-rock interactions or by contri butions of oxidized carbon with meteoric waters (Souza et al, 1995). The magnesites of the Ibor Group also show isotope values similar to those found in rocks which have been altered by hydrothermal wa ters such as those found in mineralizations of cave deposits formed by hydrothermal fluid flows (Bottrell et al, 2001). The studied rocks have undergone several diagenetic events and, thus, isotope values may not correspond to the original isotope values, but rather to those resulting from interactions with later post-depositional fluids.…”
Section: Magnesitization Eventmentioning
confidence: 53%
“…3) and will be controlled by local influences such as the original d 34 S of fluids, water-rock interactions and potential mixing processes. Bottrell et al, (2001) found d 34 S ranges of +9.8 to +13.3‰ in gypsum floor crusts from Cupp-Coutun/Promeszutochnaya cave system. While these values are similar to those identified in this work, the geological setting is totally different with no upwelling of basinal brines identified at Jenolan.…”
Section: Results X-ray Diffraction Mineral Identificationmentioning
confidence: 89%
“…3). These results contrast with more depleted isotopic signatures of bat guano from Cambodia with average d 34 S of +6.8‰ (Hosono et al 2006 The influence of hydrothermal fluids or sulfidic groundwater in gypsum precipitating karst systems has also been described (Bottrell et al, 2001;Galdenzi andMaruoka, 2003, Onac et al, 2009). However, the potential range of sulphate-d…”
Section: Results X-ray Diffraction Mineral Identificationmentioning
confidence: 94%